(untitled) - HARI PANGESTU, TITIK (Language Horizon: Journal of Language Studies, 2014)
Confession without Borders: 1st Wave Feminism against Woman’s Right Disproportion in AtiqRahimi’sThe Patience Stone TitikHariPangestu English Literature Faculty of Languages and Arts State University of Surabaya Titik_hari@ymail.com Diana Budi Darma, SS. M.Pd. English Department Faculty of Languages and Arts State University of Surabaya Dianabd9@gmail.com Abstrak Penelitianinimemfokuskanpadaketidakseimbanganatashak-hakperempuan di Afghanistan denganmenggunakantindakantokohutamadalam novel inisebagaisumberdalamtesisini. Ktidakseimbanganhakmunculsebagaiakibatdaridominasisatusisikesisi lain. Masalahpertamadalamtesisiniberbicaratentangdominasilaki-laki. Yang keduamengungkapkanpengakuanperempuansebagaicerminandarifeminismegelombangpertama. Dalammenjawabpertanyaanpertama, penelitianinididukungolehteoripatriarki, sertadidukungolehbukuNawal El – Saadawi, dimanabukuiniberfokuspadadominasilaki-laki di wilayahArab. Permasalahankeduaakandijawabdenganmenggunakanteoridarifeminism, yang mengkhususkanpada feminismgelombangpertama. Analisisiniakanmenunjukkanbahwaketidakseimbanganperempuandisebabkanolehadanyawarisan agama danbudayasecaraturuntemurundalamkomunitasini. Setelahmenggambarkandoominasikaumpria, selanjutnyatesisiniakanmenggambarkanbagaimanaperempuan di wilayahinimenghadapiketidakseimbanganini. Tesisiniakanmengemukakan,sistemPatriarki yangdinilaisebagaipenyebabmunculnyaketidakseimbangantersebut,.Ketidakseimbanganinimemberikantekananbesartercermindalampengakuanistri, yang padaakhirnyamemberinyakekuatanuntukmelawanterhadapketidakseimbanganini. Kata kunci: Patriarki ,FeminismeGelombangPertama Abstract This study focuses on depicting Afghan women’s rights disproportion by using main character’s act inside this novel. Right disproportion appears as a result of the domination of one sides to the other. The first problem talks about the domination of men’s. The second reveal the women’s confession represent first wave feminism. In answering first question, this research is supported by patriarchy theory, and supported by Nawal-El-Saadawi’s book which focus on men’s domination in this region. The second statement of problem will be answered by using a theory from the first wave feminism. The analysis reveals the disproportion of women right caused by hereditary thought of their religion and cultural and also how women in this region face this disproportion. Patriarchal believes is use as a cause of the disproportion. Furthermore, this disproportion which cause a huge pressure analyzing by wife’s confession finally give her a power to fight back against this disproportion. Keywords: Patriarchy, First Wave Feminism INTRODUCTION Offending to women in the society, especially to traditional system, it must dribble a fact of disproportion of women within it. This fact finally grounds the responder of it, especially to whom it may concern with cultural study to talk to. Besides that, this phenomenon also creates an unforgettable experience to author to write it down in utterance of beautiful work, especially novel that brings conflicts in detail. According to Rene Wellek and Austin Warren say that literary work is the representation of the author toward social life and society (Wellek & Warren, 1949: 90). According those quotation, literary can be affected by society because the author is part of the society. His idea can come from his or her society. The author combining his experience with some fiction than use this as the main source of literary works. In other word, between literary work and society or social life is tightly related each other. By using particular literary work, a researcher can identify a social condition in a particular area. Empirically, women are seen as the weakness subject. They are only put in in the second position in this life. Their duties only focus on domestic area such as bearing a child, cook for the household, and clean the house. Functionally, in war era women are only used for king and warrior sex satisfaction. They do not have any important role struggling for the war. Women’s involvement in the war seen as a problem. They are seen as the weakness creature that will cause difficulties and also seen as a stupid creature who does not understand about war strategy. So, in this era, they were only used as the object for the warrior’s sexual desire. Institutionally women are consider as the womb of baby child before it is born to the world. Unfortunately after their birth, the right of their naming is totally in their father hands. For example, in Chines system of family name, the structural of their kids name is come from their father family name. From those explanation, it can be conclude that women only seen from their function rather than their role. Women do not have their own in making important decision, to give their opinions, especially deliver about their feeling. They cannot live with their own will. Their man is the center of their live. They have to fulfill what their man need. This Traditional gender role cast men as rational, strong, protective, and decisive. They cast women as emotional (irrational), weak, nurturing, and submissive (Lois Tyson, 2006: 84). Men is the leader of their women, they have total control in decide how the women behave and act. However, in fact this traditional gender role still occur in this modern era, especially in Middle East country such as Afghanistan. This country known as an Islamic country which is uses Koran as their main laws, and guidance of their live. In Koran. Islam had been stated that "Men are the protectors and maintainers of women, because God has made one of them to excel the other, and because they spend from their means. Therefore the righteous women are devoutly obedient and guard in the husband's absence what God orders them to guard. It is also said that men are little bit higher than women and they are oblised to protect and save the women. Patriarchy has become an inevitable issue of the growth of Afghanistan as a Muslim country. Especially during the Taliban leadership, which began in 1996 till 2001. Taliban as a part of Arabian world has different perception in apply Islamic laws. The Taliban's version of Islam appears too many Muslims to be a new-born faith developed, canonized, and interpreted by Taliban scholars with the reclusive supreme leader, Mohammed Omar at the helm giving his stamp of approval for implementation. Afghan women were forced to wear the burqa at all times in public which is quite different with burqa from Arabian women. Afghan women cover all of parts their body including their face except their eyes area. Taliban see face of a woman is a source of corruption for men who are not related to them. In a systematic segregation sometimes referred to as gender apartheid, women were not allowed to work, they were not allowed to be educated after the age of eight, and until then were permitted only to study the Qur'an. Women were beaten for showing a bit of ankle or wearing noisy shoes. They could not speak in public or to men who were not relatives. They were beaten, even killed, for minor violations of these rules. But all of that oppression does not make women in Afghanistan hate Taliban men. Marrying Taliban warrior seen as one of the pride in their life. It cause the Taliban warrior seen as the hero in Afghanistan. They were struggling for their freedom from the western shackles, even in fact their coming give another suffering for women in Afghanistan. Marry them can increase the assessed value and the social status of a family. They will be considered as a family of heroes who fought for his country. So, it is pride for any Afghanistan women to married a Taliban warrior even they know what kind of consequence that they will face. Finally, it sharpen to a problem about the relation of them, Islam, Taliban, Patriarchy, and women in the world, especially to the facts reflected in Atiq Rahimi’s The Patience Stone. Generally, religion have a patriarchal view of the relationship between the genders. The relation between Adam and Eve how many religion view woman. As Al-Hibri writes, God was declared male, and man was declared to be created in His likeness. Eve became the symbol of temptation and sin. The woman was consequently judged as a less likely candidate for salvation and an everlasting life in heaven than man. (Al-Hibri, 1981:176). Islam inherited the old image of Eve and of women that depict them as the close followers and instrument of Satan, the body of women being his abode (Saadawi, 2001:274). So, it is important to envelop them in veils and flowing robes (Saadawi, 2001:275). As the living carrier of the danger of sexuality and its infinite social destructive forces, women have to be controlled. Since Islam regards women as an active sexual power, it is important to restrict women’s sexual power over men. The result is isolating women and men in different worlds. In talking about women’s oppression, feminism thought as the appropriate philosophy in investigate this phenomenon. Feminism is an awareness of women’s oppression and exploitation in society. This theory is struggling to achieve dignity, rights, and freedom for women to control their lives and bodies within home and outside. According to its movement, this philosophy were divided into three waves, first wave, second and third wave. First wave is concern about equality, second wave concern about the commitment of diversity, and third wave concern in diversity in specific normative. And according to the problem which is appear in the explanation above, the first wave movement of feminism, is appropriate movement that will be used to answer this question. Originally it focus on the promotion of equal contract and property rights for women and the opposition to chattel marriage and ownership of married women (and their children) by their husbands. This movement begin with Mary Wollstonecraft’s Vindication of the Rights of Woman (1792). Wollstonecraft’s was the first to issue an outspoken rallying cry to middle-class women, especially mothers, as major influences on society (Gamble, 2001:15). Her emphasis was on the need to make women rational, till women are more rationally educated. Furthermore, this thesis will become a great analysis when it is known that the object of this thesis, AtiqRahimi’s The Patience Stone, is the winner of prestigious Goncourt Prize in France, and is a deceptively simple book written in a spare, poetic style. It is rich read, part allegory, part of tale of retribution, part an exploration of honour, love sex, marriage, and war. It is without doubt an important and courageous book. This voice is in giving voice to those who, as the fable goes, suffer the most and cry out the least (Khaled Hosseini, The Patience Stone’s Preface). The Patient Stone is a France novel which is translated in English version. Set almost entirely in one room - the bedroom of the husband and just about the only character who talks is the wife. The woman open up her feeling and thought to the men in her society, confronting the taboo of female oppression and sexuality. Her voice can describe the darkness in her live, her painful and her sorrow for being as a women. Her monologue definitely drive out the reader to think as the woman side, without eliminating the other character in this novel. Besides The Patience StoneAtiqRahimi also wrote some canon novel and won some prestigious appreciation. The first novel is Earth and Ashes, written in Persian and become an instant best seller in Europe and South America. A movie based on this book, directed by Rahimi, was awarded the Prix du Regard versl'Avenir at the 2004 Cannes Film Festival. The film was featured in 50 festivals, winning a total of 25 awards including the one at Cannes and a Golden Dhow award for best feature film at the Zanzibar International Film Festival. And the others work is A thousand Rooms of Dream and Fear. Working on disproportion of women right for study is always an interesting and courageous idea. Through the confession of “Wife” character in this novel, this study can reveal that there is a rebellion and courageous, and how this character survive from the disproportion in Taliban era. Wife already thought since she was young that man is leader for woman, so she must obey him. Rather than fight back against her husband, she choose to use her silence as a form of rebellion. By using this character, it is can be seen that there is a rebellion inside of hereditary understanding regarding woman and man positioned. With discussing this topic, there is a description about what happened in this country especially about the inequality and also how far the disproportion of the women right still exist in this country. RESEARCH METHOD As has been stated in the description above, literature is a reflection of a society portray and the combination of the author fiction. Literary work is meaningful. Hence, it delivers many meanings and interpretations that can be caught by the reader as an interpreter. In other word, to find the accounted result, it needs a method that is based on the problems to avoid the blurry result. This study take novel from Atiq Rahimi The Patience Stone as the main source, and using some quotation inside it as the data. The type of this research is qualitative research because it produces descriptive data. The problem in this study is concerning about man’s domination and woman’s inequality treatment that will be analyzed by using patriarchy and first wave feminism from several feminists. WOMAN IN ISLAM Islam already stated that man is a leader for woman so they obliged to educate, protect and maintain the woman. God had been created man little bit more than the woman. It can be seen by the existence of their muscle. This gift, make man as the stronger one so they are seen as the appropriate one to be a leader while woman is the follower. So, woman must follow and obey their husband. According to Saadawi’s book, Islam inherited the old image of Eve and of women that depict them as the close followers and instrument of Satan, the body of women being his abode (Saadawi, 2001:274). So, it is important to envelop them in veils and flowing robes (Saadawi, 2001:275). In other word, this society position woman as the guilty one dealing with their body and sexuality. That is why, woman in Islam, especially in Patriarchy country must get married, so they need man to control their temptation. Islam makes marriage as the only institution where sex between men and women can be done in a way that is more moral (Saadawi, 2001:280). Sex is done outside this institution directly transformed into an act of sin and evil, even masturbation was not permitted. Based on Ibnu Abbas’ (friend of Prophet Muhammad) statement “and married a slave is better than masturbation and fornication (zina)”. Therefore an unmarried men divided into three sins, first married a slave, then masturbation the foremost is fornication (zina). In other words, marriage is an established system for sex where one part uses to avoid slander (fitnah) and the other side used it as the legalization for reproduction as much as they want, and off course get good agreement to acquire pleasure within the bounds of Islam (Saadawi, 2001:281). Based on the Al-Ghazali an Arabian philosopher statement in Nawal’s book, besides for reproduction, the purpose marital is immunity against demons, break the sharp tip of the desire, distance from danger of lust, keep our eye from what who supposed not to be seen, protect male sexual organ, as well as follow the advice our prophet (Saadawi, 2001:276). But this institution is still different for men and women, especially dealing with their rights and obligations not only inside in their house hold but also in their society. In their household activities, wife only concern about their domestic business. Their main job only raising their children, cleaning their house and satisfying their husband in bed. They do not allowed to care about what happened outside their area. Marriage makes men’s heart free from household and clean their house, so they can concern to their job, religion and science in other word, they can concern in developing themselves. Al-Ghazali states in Saadawi’s book “In fact, your wife let you to work on the final day and she concern about your house and relieve your lust” (Saadawi, 2001:284). Therefore, a man is seen not able to devote themself in science development and religion unless they have a wife that can handle their household. ARABIC SOCIETY Arabic culture is male centered. Males dominate most cultural, political and social institutions. This has a direct impact on the cultural status of women in both Arabic and Islamic countries. While Islam emphasizes the equality of men and women, Arabic culture minimizes it. A Jewish Arab in Morocco or a Christian Arab in Syria adheres to the same system and thus would have the same views on the role and status of women. The socially-rooted conceptualizations of differences in women’s and men’s sexualities and their biological nature are so frequently evoked to the extent that they become part and parcel of the individual and collective consciousness. In this regard, the “natural role” of women is one of the most deeply rooted interventions at the conscious and unconscious levels. Consequently, women’s fulfillment of their “natural role” associated with the reproductive process becomes compulsory and coercive. In the end, this leads to women’s lives becoming regulated through the sharia, constitutions, laws, and predominant social norms, in ways that far exceed what applies to men. In Arab societies, women’s status is mainly defined by their roles as mothers and wives. Their main job only concern about raising children, cleaning their house and also serve their husband (Saadawi, 2001:285). Different from the husband's position as head of the family, they are taking control over their families, so that the actual duty as a husband in this culture region is to control and supervise the family and finally it position woman in second position after their husband. Women could not make decisions based on their own beliefs, and had little control over their marriages. Society create that the noble obligation for a wife to completely obedient to their husband, they cannot be different, no asking a question or refused their orders, (Saadawi, 2001:286). In other words, there is no independent decision for women. Their freedom is limited or moreover it is deleted because the ideal women in this society is a woman who can follow her husband without complaining about anything. Essentially. So, it can be conclude women were slaves to men and made no decisions on anything, whether it be something that directly impacted them or not. LOVE AND SEX IN ARABIC SOCIETY The strong influence of the cultural background of the Arab and Islamic values which strongly stuck in Arabic life makes this nation see love and sex as something taboo and full of mystery. In this region, woman take crucial part in this ritual. As the legacy from cultural background and also religion values the Arabic seen women without exception as cause of fitnah (fornication). Arab woman adorned with temptation and fitnah. Where in this sense they become part of the spirit of Islam, which force women into sexual temptation in the community who bring libel. In this case is related to a conspiracy libel, resistance, which interfere with any order that has been built by the gods. So, they are very closely related to sex and sin (Saadawi, 2001:273). Men on the other hand, though had great sex appetite, not accused of sin unless driven by temptation and seduction of women. The power of the male sex being a part of the soul of the Arabs and its soul is connected with virility (Saadawi, 2001:294). Thus, man is ordered to marry in order to defeat the evil and the woman temptation. Despite the desire of sex are owned by both parties, but in fact women in this region bear all the restraints. Man sexuality is connected with virility different with women sexuality which their sex connected with sins and devil. So, it will be ashamed if men in this region have a problem in their sexuality that is impotent and the only one who can know this, is woman. But the solution taken upon of these problem were quite surprisingly. As quoted in Saadawi’s book “Virgins were not permitted to know far about sex, while a widow who already have experience from her previous marriage definitely can recognize this weakness. That is why they give “Lower” for their label” (Saadawi, 2001:295). These restraints were taken up in order to protect men from women so they cannot drop them. Women must keep their virginity by their own self. A woman who lost her virginity before marriage will be confuse and fear of family rejection both from family or society, but men who come save her will be seen as a hero and respectful (Mernissi, 1999:86). In a marriage, blood of virginity is very important. In the first night after their marriage, commonly they will use white sheet in order to see virginity blood and this blood is an evidence of chastity and honor of family (Saadawi, 2001: 295). Contrary with men who cannot be identified their virginity from their physical and the limitation of the girls knowledge about sex, it makes them do not have any burden even they already ever had sex out of the marriage. So it can be said that Arabic society were more tolerate to men in their sexuality rather than women. Beside virginity blood, the other blood which is very crucial for Arabian society is menstruation “haid”. In Islam haidseen as a dirt. In an authoritative Arab dictionary named Lisa Al’-Arab menstruation mean al- khubts (Viciousness combined with cruelty), al-makr (the desire to destroy been prepared with despicable). Menstruation for women is related with their sexuality. They are seen ready for their sexuality when they already in this period. So, when they arrive in this period, in Arabian culture means that their temptation was completed. And based on Surah above women in this period time were seen as the impurity women. PATRIARCHY IN TALIBAN When the Taliban took control of Afghanistan in 1996, the status of women declined rapidly until women were completely confined to home, or only allowed to leave home with a male escort while wearing a burqa. If a woman seen outside without being covered from head to toe, even if only a little skin was exposed, she would be beaten. These rules complicated things completely for women who no longer have a living male relative, or women who are too poor to be able to purchase a burqa.The other extreme rules confining women during Taliban are, the window in homes to be painted to prevent others from viewing women from the outside, women must not laugh, talk loudly, or make any noise at all when in public. All of these rules among others made women prisoners in their own homes, unable to go anywhere or do anything without being under the watch of man. Based on the explanation above, it can be conclude that there is a disproportion of rights in this sexes. The sense of patriarchy is definitely appear in regime. Taliban imposed straight rules for women or it is also can be said they tend to jail women., limited their access, hide them from worldwide and also do whatever they want to women. According to Millet, patriarchy’s chief institution is family, where patriarchal ideology well maintained traditionally and modern. As the smallest unit, family contribute in strengthening this ideology (Millet, 1970:33). Encourage every family members to think and behave in accordance with the rules of the community who embraced the patriarchy. In this institution, commonly this ideology will be It will be taught into two categorize, that is how girl’s role and boy’s role. They will learn character, role and status between wife and husband and also father and mother. According to Millet, patriarchal ideology socialized into three categories. First, temperament involves the formation of human personality along stereotyped line of sex category ("masculine" and feminine), based on the needs and values of the dominant group and dictated by what its members cherish an themselves and find convenient in subordinates: aggression, intelligence, force, and efficacy in the male: passivity, ignorance, docility, “virtue” and ineffectuality in the female. This is complemented by a second factor, sex role, which decrees a consonant and highly elaborate code of conduct, gesture and attitude for each sex. In terms of activity, sex role assigns domestic service and attendance upon infants to the female, the rest of human achievement interest and ambition to the male (Millet 1970:26). Patriarchal ideology is very difficult to remove from this society because they still maintain it. Stereotypes attached to women as domestic workers made ??him weak because they did not get money from their work to take care of the household. Domestic work is taken for granted and it was her duty as a woman. She does not need to earn money from their work and the result she always dependent on her husband. Millet stated that patriarchal ideology cannot be torn down because women are economically dependent on men. Dependence that occurs throughout life. Conventionally men are the main source of income in the family while the woman is the housekeeper. Men worked outside for their economy and women living at home to do all the housework. Women are not allowed to make money, because men make it as property when they got married (Millet, 1970: 40). In a patriarchal system, men have full power to women so that they can do whatever it wants with his wife. Women economically dependent on her husband because they did not earn his money out of pain. According to De Beauvoir, regarded as a slave wife, while the husband is her master. This can lead to the occurrence of domestic violence (Beauvoir, 1989: xv). FIRST WAVE FEMINISM Feminist theory addresses two fundamental differences in the view of women and men. Expression of male-female differences in the biological aspects of the show as the essence of natural, innate. While expression masculine feminine is psychological and cultural aspects of difference (Megawangi, 2004: 184). Si mon de Beauvoir stated that in a patriarchal society, women are placed as the “Other”, as second-class human beings, lower by nature (Selden, 1985: 137). Position as the “Other” affect all forms of social and cultural existence of women (Cavallaro, 2001: 202). Patriarchal society using a certain fact about the physiology of women and men as a basis to build a series of identity and masculine and feminine behaviors are enacted to empower men on one side and women on the other weakens. Patriarchal society convince themself that the construction of culture is "natural" and therefore "normality" depends on one's ability to demonstrate gender identity and behavior. This behavior is culturally associated with one's biological sex. Patriarchal society uses rigid gender roles to ensure women remain passive (loving, obedient, responsive to sympathy and approval, cheerful, kind, friendly) and men remain active (strong, aggressive, inquisitive, ambitious, full of plans, responsible, original, and competitive) Meanwhile, according to Millet, patriarchal ideology in academia, religious institutions, and family justify and affirm the subordination of women to men who lead for most women to internalize self to men (Millet, 1970:26). One way to understand the various dimensions of feminist theories and their theoretical approaches to understand patriarchy is to locate them within the broader philosophical and political perspectives that have been broadly classified as first, second and third feminism movement. This theory were categorize in three waves according to its concern about. First wave is concern about equality, second wave concern about the commitment of diversity, and third wave concern in diversity in specific normative. However, there are some ideological differences among the feminist groups, they are united in struggle against women inequality and hierarchical relationship between women and men. To be more focused on equality of women phenomenon, the first wave of this movement thought as the appropriate approach in analyzing this issue. The first wave of feminism took place in the late 19th and early 20th centuries, emerging out of an environment of urban industrialism and liberal, social politics. The goal of this wave was to open up opportunities for women, with a focus on suffrage. The feminist in this movement assumes that there is basically no difference between men and women. Therefore, women should have the same rights as men. Nevertheless, liberal feminists reject the overall equation between men and women. In some cases remain distinction (distinction) between men and women. However, the function of the female reproductive organs logical consequences in social life (Ratna Megawangi, 1999: 228). Mary Wollstonecraft is one of the pioneer for this movement. In her book Vindication of the Rights of Woman (1792) she talked about her life and personal significance as an icon of the women’s movement. Wollstonecraft’s was the first to issue an outspoken rallying cry to middle-classwomen, especially mothers, as major influences on society (Gamble, 2001:15). Her emphasis was on the need to make women rational. Far from portraying women as superior to men, Wollstonecraft wanted to raise their overall moral and intellectual stature to make them into more rational citizens. For the most part, she did not envisage their leaving the domesticsphere, nor did she ask for anything as radical as the vote. Even she accepted that women in middle-class would marry and remain at home, but she want every girls get same education as a purpose for their freedom and dignity rather than the ability to fascinate potential husband (Gamble, 2001:16). Not only Wollstonecraft who does not agree with this disproportion. Rosemarie Putnam Tong in her books “Feminist-Though: A More Comprehensive Introduction” imply that there is a restriction of women’s activity and it cause they lack of power and knowledge so that they cannot develop themselves. DOMINATION REPRESENTED IN NOVEL The Arabian world are very thick by the influence of their culture either before or after Islam. Where both are directly or indirectly gave a special position for men rather than women. If the granting of this position was originally intended to separate human’s daily task, but in fact this positioning has grown to become a leader and the led. Develop as the domination of one side to the other sides. Through this novel, this domination will be exposed as a reflection of the real condition in the country inside this novel. In this region Patriarchy ideology has been used as root for society structural in this region. This ideology still maintained in this modern era, make this ideology quite difficult to be changed or removed (Millet, 1970:40). Since their a little, boys and girl were already given an example by their parents behave, and when their already in their puberty time, they were thought how man and woman behave, and unconsciously differentiate them in two different position. As an example in this passage, ‘When I got engaged, I knew nothing of men. Nothing of married life. I knew only my Parents. And what an example! All my dad cared about were his quails, his fighting quails! I often saw him kissing those quail but never my mother, nor us, his children. There were seven of us. Seven girls starved of affection (Rahimi, 2010:57). In this passage can be criticize that family is chief institution for this ideology to get developed. Family has huge contribution in strengthening this ideology. According to this passage, her family was the only example for her to understand about how is marriage life. Her father only care about his quails and never the girls and also her mother, but she never saw her mother complain about it. Made this situation seems normal and that how it was supposed to. Wife should not disturb her husband, especially complaining about what they do. Because wife’s job only concern about their household and fulfill husband’s satisfaction (Millet, 1970:40). Concerning about husband satisfaction, letting him do what they want to do can also meant as an effort in satisfying her husband and women is this family was supposed to be quite and submissively. In this group, women are defined as something odd, deviate from a prototype of human’s body, physically passive and contain of emotional, different with man’s body who have active and ably mind result a conclusion that women considered as a carrier for men’s seed, so the real creator is the men (Millet, 1970:54) As what the author had been explained above, men is leader for women because God create them a little bit more than women, so they should follow their command. (Back to the passage ‘Look, I breathe just like you! (Rahimi, 2008:7), and also in the passage “You know that I live only for you, at your side, by your breath” (Rahimi, 2010:9). Through those passage, women should follow their husband in every way. They led them in every case, metaphor with “breath” which can be meant that women should follow them in every way, and bow down to their rule (HR. Tirmidzi verse. 1159). Women must following the rhythm of their husband breath, walk inside their shadow, and hide behind their shoulders. It is also mean that men are take control of women’s life. Mean have a charge to change the rhythm to their breath or even stop it when they want it, it is all their right, and women should follow them. No asking and complaining as can be seen in this part ‘I hope you are able to think, to hear, to see…to see, and hear me…’ (Rahimi, 2010: 52). This part can be used as a reflection that women in this society do not have a voice to deliver their feeling, never have a chance to be thought, and seen as the important subject. Those description can be used as the early indication about how men dominate women’s life in this region especially in their marital section. Human in this region separated into two different world, women’s world and men’s world. As the author already said, men have their special world as a heritage from their culture and also their religion. Men in this regime do not have any straight boundaries. Start from how their outfit and also how they behave. Different with women which have to concern about what they do, and how they do it. Man created a little bit more. It can be seen with their muscle, where muscle is related with physically power, and finally spread in many aspect. In other hand, women who are created without muscle are directly related to the weakness and finally prison them in domestic job. The differences of their body led different attitude towards both. Women in this society who does not penis considered less than man is seen as the embracing one. Penis who located in outside seen as sign of autonomy and power, while women’s genital are putted inside and hide (Beauvoir, 1989:18). As an example in this novel ‘I was a piece of meat, into which you could stuff your dirty dick. (Rahimi, 2010:112). According to this passage penetrate woman also can be meant show their authority and power while woman only used as a bowl to put this power. According those explanation, women in this ideology were putted in inferior position which mean that they only putted in second class. Their existence indirectly eliminated in this regime. In order to keep maintain this existence patriarchy ideology woman only have one conditional, that is companied by her mahram, or husband (Beauvoir, 1989; 225). Patriarchal society provide scary threat for women who is living without men beside her. As can be seen in the page 17 in this novel, ‘And you leaving him in this state? What about his children? And me? You can’t, you can’t, you‘ve no right to leave us like this, without a man!’ (Rahimi, 2010:17). In this passage, wife feels afraid if her husband died and let her alone. It is because she will be left alone, not only by her husband but also because of the society and her family. Hence, they should get married. Women in this ideology does not allowed to choose their husband. As can be seen in this monologue before her marriage, her mother-in-law came to her house and asked her to married her son (Rahimi, 2010:53). According this passage, women in this region do not have any right to choose their husband. Her father or family never asked about her opinion or her criteria about her ideal man, and accepted without slightest hesitation. In contrary, men can choose which one they want to get married. Married in this region also can be criticized as a transaction. They used Maharas a tool in this transaction, (Saadawi, 2001: 283) a transaction between abolishing family anxiety because of their virgin daughter and find the legality of fulfillment of lust. But if be observed further marriage can be said as announcement for their leadership, and independence for a man, different with the women. As the consequence, a virgin who agree to get married must throw their freedom and get ready of any rules that had been made by her husband. When a man had married they have a freedom in sexual intercourse that just being a story when they were teenagers. They also allowed to set up a small country named family that ultimately gave them a power. And women, unconsciously walk into a trap which restrictive their freedom as seen in this part, ‘Three years! For three years I wasn’t allowed to see my friend, or my family…It wasn’t allowed to see my friends, or my family…it was considered proper for a young married virgin to spend time with other married women. Such rubbish! (Rahimi, 2010: 54). This passage can reflect the exile from the association in women side, different with man which does not any significance differences, or limitation of their association. Seems like marriage is also a way for them develop themselves about science and knowledge, as an example is a war. Commonly when a women marry because of arranged marriage, usually their marriage are not based on love. For woman in this ideology love is not always about feelings, but also about the commitment throughout body and soul unconditionally (Beauvoir, 1989:526). In fact love is very important for a woman, they can sacrifice anything while she did not realize that this feeling can make her suffering. Love can be illustrated as an essence of sexual oppression for women, because men can used it as cultural power to dominate women (firestone, 1972:121). As an example, when wife decided to accept her mother-in-law proposed “Who were you, really? No one knew. To all of us, you were just a title: the Hero! And like every hero, far away. Engagement to a hero was a lovely thing, for a seventeen- years-old girl. (Rahimi, 2010:54). She directly falling in love with someone that she never known before. The reason was because of he was a hero, and it was a lovely thing married with a hero. But in fact, this love unconsciously made her sacrifice her freedom, and prepare to be a slave for her husband. He use her love to satisfy her lust, to bear their child and to clean and prepare for their meal. Love beat the rational thought of women, it was realize that the bride got married without her groom presence, ‘At the ceremony, you were present in the form a photo, and that wretched khanjar, which they put next to me in place of you’ (Rahimi, 2010:54). In this snippet of her monologue can be interpret the importance of man in women life. Even they have to marry with a strange men, whom only known from his photograph. This stage of live can be said as the place where patriarchy is definitely felt by women. Men have huge chance in developing their self because the already have wife who will concern about the domestic job (Ghazali,IhyaUlum ad-Din, 1964:699).. As reflected in this passage ‘Did you think about us for even a second, when you shouldered that fucking Kalashnikov? You son of a…’.the word suppressed again. (Rahimi, 2010:14). This passage can reflect that husband only concern about his struggle toward his enemy. Totally concern about his war, without understand his family. He throw domestic responsibility to his wife, and use her natural fate as his justification. Women should run in her roles as a wife who must serve their husband, bear a child, and satisfied her husband in their bed. This ideology see everything including about women with the male point of view (Beauvoir, 1989:xx). By using men likeness or dislike, patriarchy ideology make rule and prison them under men feet. As can be seen in this passage, It was not considered proper for a young married virgin to spend time with other married women, (Rahimi, 2010:54). Based on the passage above, woman could not see her friend or more is gossiping about many thing. Gossiping is not allowed in Taliban regime, because they see it as something useful. But if it see deeper, they are not allowed to see their friend especially among marriage woman because they afraid of being betrayed. Men never directly deliver this fears, they hide it hereditary. That is why they used this banning as law in their family. They use women’s fear to control their behavior. And women who hereditary not rewarded by any right against her husband, do not have any effort except silent and following their command. Beside become the follower for the men, this region also put woman as place for bearing a child. This society make that women should birth a child, because it is their natural faith, and with that you will be the perfect women. So, it will be a huge problem if woman is infertile, they will be seen as imperfect or unideal woman because she cannot fulfill her nature destiny as a mother, she face divorce threat, and get low view from her society. As can be seen in aunt character. She got divorce because she cannot bear a child, and finally get exiled by her family. Society unilaterally blame her without care with her feeling and sadness because she cannot perfect as a woman. Different in man sides. If woman have their infertile problem, man will feel ashamed if he is impotence. But through this novel, it is not a big deal for men because the society seems like protect them for their weakness. In this novel there is a big secret that had been hidden since their marriage, the secret that only known by wife and her mother in–law. Start from her mother in-law unilateral decision that she was barren, ‘Your mother had decided I was barren, and kept hassling me all the time’ (Rahimi, 2010:65). From this part it can be used as an identification that in this region woman is the most important part in bearing a child, without care that woman also need man so they can bear a child. They blame all in woman shoulder, and try to find a solution as an interest of a descendant. And polygamy is the able solution for this case. Polygamy is allowed by the religion and of course make man have a big smile because of this policy. As reflected in the passage ‘Your mother was dying to see you to take a second wife’ (Rahmi, 2010:66). Based on this monologue, her mother in-law only concern about the real function of woman as a child bearing rather than a human. However unexpected situation came up and reveal that her husband is the infertile one. ‘Because that child was not yours!’ She falls silent, impatient to see her man finally crack. (Rahimi, 2010:131), ‘Yes my sang-e sabur, those two girls are not yours! ‘She sits up. ‘And do you know why? Because you were the infertile one. Not me!’ (Rahimi, 2010:132). The fact is, now they have two beautiful daughters and they are their real parent. Nobody know the secret except those women. Seems like everything was fine, and they can fulfill their natural fate. But if it is seen deeper, they create this scenario in order to keep save a husband. After her mother in-law knew that hers son is the weakness son, she did something that is contrary with her religion. She sent her to a Hakim, a kind of shaman until she is going to pregnant, as reflected in this passage ‘She spent a lot of cash that day, I can tell you. And then I visited the Hakim several times, until I feel pregnant. As if by magic! But you know what, that Hakim was just my aunt’s pimp. He mated me with a guy they had blindfolded ‘(Rahimi, 2010:132). The mother-in-law was willing to do anything for saving her son from bad view of social groups even she have to turn aside from her religion. In contrary with wife’s aunt, because she is the infertile one, her family never look for a solution to save her, but they directly throw her from her family and forget about her. From those example can be criticize that society give a huge tolerant for men, gave more privilege to be understanding for their weakness. Hereditary it is done by the society. Give men some privilege either it is openly such as polygamy or closely by protecting their weakness. By sacrificing women’s feeling. This condition finally raised women’s anxiety for her husband satisfaction. According to this passage ‘Although it often seemed to me that you weren’t satisfied. And then I would guilty. I told myself that it was my fault, that I didn’t know how to do it right. (Rahimi, 2010:105). According to this passage, wife feels guilty because of she believe that she cannot satisfied her husband. It was her fault because she believe that it was her duty as a field for her husband. Lacking of sexual knowledge make her blame herself (Saadawi, 2001:295). But after have several sexual intercourse she realize that it was her husband weakness, ‘After a year, I discovered that actually, it was all coming from you, you gave nothing. Nothing’ (Rahimi, 2010:105). Now he can find her husband weakness, but because of her position as woman which is does not have any voice, make her only keep inside her mouth. In sexual intercourse, although it was done by two subjects but in fact man is taking control for any movement or position in this intercourse. It because man is a leader for woman according to the religion. State by Al-Hasan an Islamic scholar in Saadawi’s book state that man does not allowed to fulfill his woman command because he will throw into hell in the judgment day (Saadawi, 2001:286).In this monologue “If I’d asked all that to you…my God! I’d have got a broken nose! And yet it’s not difficult…you just have to listen to your body. But you never listened to it (Rahimi, 2010:111). A woman can't make a favor though is aimed for their satisfaction. Women only follow the men, but in the end blame themselves if the husband feel unsatisfied in this intercourse. If in their personal intercourse, women must keep silent how about their daily live. Monologue above can used as the example that women in this region are completely silent. They feel afraid because they will get a punishment because of their favor. Men are allowed to beat their wife after they do advise and forsake them from bed. But in fact, for any reason that make her husband angry, he will directly beat them. As an example in this monologue, ‘He beat up my mother, my sister and me, because we hadn’t kept watch over his quail’ (Rahimi, 2010:60). Her father beat them without clear reason. Because of he cannot find his quail make him angry and find an impingement. It is can be seen that his father forget about several steps before beating her wife, he only see “beat” word which is mean it was legally done by any chance. From those example above women in this region had already knew that marriage is not always beautiful like what they thought. But because of they live in patriarchy circle which put men as the central part make women in this region, completely need men. It would really frighten for a woman living without a man beside her, although it was just a name. In this novel wife only live with her husband name for three years, she must deal with her husband absence as a consequence having a hero husband. But it is fine for her, because she now has a man beside her, have somebody who is believed as her guardian, give her a distance as an accusation of temptation carrier. But when the husband back in a dying state and his wife, are required to maintain him, she still afraid of her society view, especially threat of widowed. In her monologue she stated ‘She stands up. ‘Even injured, you’ve been spared suffering’ (Rahimi, 2010: 21). It can interpret even her husband lay down, suffering because of the shot, he never feel suffer because all of social cruelty come to her. She is afraid if her husband died brother in-law will come and harassing her. Afraid for become a widow and get exiled from her family. In other words it can be inferred that marriage is very important for a woman in compare man. Without marriage, which also mean that there is no man beside her, woman cannot retain their existence as part of their society. Excommunicated by the negative view about woman that hereditary this society inherited either from their religion and cultural background. Without marriage they will be seen as a devil with the temptation inside it. The devil who can bring trouble for their family and society. Always seen as the imperfect creature, which full of dirt and irrational emotion. CONFESSION WITHOUT BORDERS AGAINST DISPROPORTION Essentially, gender differences are not a problem as long as this difference create discriminative for one sides. There is a significance differences of the rights between women and men in this patriarchal world. Men are placed as the central, leader, and finally named as “The self”’ while women who is seen physically weakness later differentiate as “the other” (Selden, 1985:137). As can be seen in this quotation, “There were seven of us. Seven girls starved of affection” (Rahimi, 2010:57). In this quotation, this girls feel starving of affection, although they have complete family. By using Selden’s quotation above, seven of them feels less of affection because they do not get a figure of a father, in other hand their father only concern about his quail, and love it more than his family. This cold attitude can be seen as a disappointed feeling because they do not have a son, a son that can be a symbol of power, and heir his leadership. In other word, he see women as the unimportant one. As a formed of this disappointed, he use a quail. A quail is better than women, at least his quail can won and be a subject that he can proud of. In this regime, women in this region is not more meaningful rather than a display, ‘She is still laughing. ‘That story is so true. “You men! As soon have you have guns, you forget your women.” (Rahimi, 2010:57), same like the theory about “women as the other”. According this quotation, women are alienate with inanimate object or this inanimate is more prestigious than a women. When she speak about it she is laughing, this laugh can be seen as an expression that she has same level with that thing. But she cannot do anything against this attitude, except smile as her laugh at her sex bad destiny. Since in childhood she always alienate with inanimate, either with quail or a gun the positioning of women as “the other” has been tough since their childhood (Nunuk, 2004:76), so that they will adapt and unconsciously get usual with this called. According this situation it also can be imply that Family played a major role in this believed (Millet, 1970:26), parents become main teacher of this situation, especially mother who is seen as the real example for her daughter. In this region, where women performed as en-soi(Being-in-itself), while men performed as pour-soi(Being-for-itself) (Tong, 1998:181) will attempt to free from men’s pressure. This is how was the normal human will struggle when they were in huge pressure. ‘At that time, I was only ten …no…’She thinks about it. ‘Yes, ten years old. I was scared. Scared that I too would become the stakes of a bet. So, do you know what I did with the quail?’ She pauses a moment. It is unclear whether this is to make her story more exciting, or because she is afraid to reveal the next part (Rahimi, 2010:59).She was afraid, a quail is a danger for her. If it was lose, she will sent to live with a man like what happened with her sister. So, she will do anything to eliminate this danger. According this passage, there is a power inside this women’s silence. She eliminate the quail to keep save, hope that by killed that bird she will not be used as bet. Using theory from Sartre, when there is a subject trying to free itself from the other, there is another subject who want to enslave it (Sartre, 1956:362). When her father trying to enslave her by using her as a bet, or beat her when he lose he find a way to free from him, that is by killed his bird. Started from this step, she finds a way to still save. And when she had enough to marry, she choose it as a solution for her to free from his father, but in fact after she got married, her husband enslave her. He put her as place to fulfill his sexual and also rearing a child. In other word it can be conclude that marriage is not a place to get a freedom, it is a form of slavery (Beauvoir, 1989:500). It is ultimately wrong if this society put women as the weak and fool creature only by using the weakness of their body. Because of they do not have a muscle and penis which always as a form of power because it penetrate women, does not mean that they are fool (Beauvoir, 1989:41). It is not enough use their body as the reason to put them as the inferior one. In those quotation we can see how women ability in order to protect themselves and the people she loves. She was lying, but it is work. She did keep her husband alive from the other shoot which directly kill him. She use her brain, her ability, her experience, and also the society norm to fight back. So it can be conclude that woman is not the other because of their lack of penis, but because of their lack of power,( Beauvoir, 1989:55), or it is also can be said that they were not allowed to get this power. In other word, if women put in same position with men, they would develop the same character (Wollstonecraft, 1975:23). But because of this society hereditary thought that women is lower than men, makes them deny their ability, which finally force them to keep silence, and killed their self-development. From this confession, she hide the fact, she did not want people to know about this, because she would be seen as a demon. So she kept silence, keep hide her power but indirectly she still use it to save her. But unconsciously she confess to her husband while he was lying powerless. Make her afraid if her husband hear it and finally beat her without understanding what will happened to her if this quail still alive. So it can conclude, because of this society treatment, who only blame women and hereditary this sex with the foulness of Eve (Saadawi, 2001: 278), they must hide it. Even use these weapons are not because they want to fight against their husband, but they use it in order to keep them save. Psychology and biological differences in the most contribute aspect in this disproportion. Men with their sperm give a life for the wife with their egg inside (Beauvoir, 1974:24), so it can be conclude that women is place while men is the real creature. CONCLUSION Live in patriarchy circle, make this women cannot do anything they want. As had been explain by the Beauvoir, women in this circle putted as passive, and submissive. Because of they are the weakness they need the superiority one to keep them as a part of this society. In other word, they need marriage to keep save inside this circle. In this region marriage can be seen as turning point that bestows prestige, recognition, and societal approval on both partners, particularly the bride. It also can be said as a social and economic contract between two families. But in other hand, marriage in this region is a new beginning of slavery that will happened to women. They have to sacrifice their freedom and concern about their household, but for men side marriage is a declaration for their leadership. And finally make them can be more focus in their self-development. Marriage is a form of slavery in all aspect related to women’s body and sexuality including blood inside them. This research reveal the importance of virginity blood that is so important for women as its used as a proved that they can keep their dignity, and it is also make them as the ideal women that deserve to be married, contrary with menstruation blood which drop them in the lowest point as a women. It is happened because this society see menstruation blood as a dirt according by their holly book in verse 2:222. This research also reveal the differences treatment between a virgin and a widow. By using Saadawi’s statement, based on the knowledge, this society limited virgin knowledge about sexuality, and widow is putted in bottom position as seen as the embracing one. This effort is taken as a way to protect men from their virility problem. So, it can be conclude that this society is more tolerant to men rather than to women. The Second statement of problem is the confession of women voiced by wife character in this novel. She reveal the real condition caused by the pressure that the society gave to her sex. Inside this confession, she deliver the disproportion that she gave in order to save her husband. As had been explained by Putnam Tong, this confession explicitly imply that she was created inside a men (en-soi), hide inside their body and shadow while men was created for their own self (pour-soi). This society believed that it was a natural faith that women must sacrifice themselves, and also follow what the leader had been said. But even it was already thought as their norm since their childhood, by using her confession this research reveal that they do not accept it totally. By using her husband dying body confess all her depress and her disappointed to her world. According her monologue, there are senses of hatred, insult, and harassment that happened to this woman, that make her angry and hate them. But because of the society will gave worse punishment to the women who against her husband who also seen as the rebellion, she only keep silence, but inside this silence she struggling by using her innocence, sexual and temptation . But this struggling is more to protect herself rather than fight back to her husband. Finally this confession make her realize what happened to her, how her society was being unfair to her. The accumulation of these unfair treatment make finally fight back and finally kill her husband by a Khanjar. REFERENCES Abrams, Meyer. H. 1971. The Mirror and The Lamp: Romantic Theory and The Critical Tradition. London: Oxford University Press. Rahimi, Atiq. 2010. The Patient Stone. London: Chatto&Windus.New Burke, Edmund. 1999. The social History of the Modern Middle East. Colorado:Westview Press. Millet, Kate. 1970. Sexual Politics, New York: Doubleday. Beauvoir, De. 1989. The Second Sex. New York: Vintage Books Shulamith, Firestone. 1972. The dialectic of sex, the case for feminist revolution. USA: William Morrow and company Inc. Gamble, Sarah. 2006. The Routlege Companion to Feminism and Post Feminism. New York. Routlege. Saadawi, El-Nawal. 2001. PerempuanDalamBudayaPatriarki. Yogyakarta: PustakaBelajar Mernissi, Fatima. 1999. PemberontakanWanita: PeranIntelektualKaumWanitaDalamSejarah Muslim. Yogyakarta: Mizan. Gorsky, Susan Robinov. 1992. Feminity to Feminism: Women and Literature in the Nineteenth Century, New York: Twayne Publisher. Tong, Putnam. 1998. Feminist Thought: A more Comprehensive Introduction. Colorado: Westview Press. Sumbulah, Umi. 2008. Spektrum Gender, KilasanInsklusi Gender di PerguruanTinggi. Malang: UIN. ARTICLE SOURCE MARRIAGE IN THE ARAB WORLD by Hoda Rashad, Magued Osman, and FarzanehRoudi-Fahimi INTERNET SOURCES www.mtholyoke.edu/-macne. www.Astyariah.com/godaan-dunia-dan-wanita.html. <a href="http://www.salaf.web.id/277